Microproteomics and immunohistochemistry reveal differences in Aldo-Keto reductase family 1 member C3 in tissue specimens of Ulcerative Colitis and Crohn's Disease - Arafah, Karim; Kriegsmann, Mark; Renner, Marcus; Lasitschka, Felix; Fresnais, Margaux; Kriegsmann, Katharina; Winterfeld, Moritz von; Goeppert, Benjamin; Kriegsmann, Jörg; Casadonte, Rita; Kazdal, Daniel; Bulet, Philippe; et al. (Proteomics. Clinical applications, 2020)
Purpose Differential diagnosis of ulcerative colitis (UC) and Crohn's disease (CD) is of utmost importance for the decision making of respective therapeutic treatment strategies but in about 10-15% of cases, a clinical and histopathological assessment does not lead to a definite diagnosis. The aim of the study is to characterize proteomic differences between UC and CD. Experimental Design Microproteomics is performed on formalin-fixed paraffin-embedded colonic tissue specimens from 9 UC and 9 CD patients. Protein validation is performed using immunohistochemistry (IHC) (nUC=51, nCD=62, nCTRL=10) followed by digital analysis. Results Microproteomic analyses reveal eight proteins with higher abundance in CD compared to UC including proteins related to neutrophil activity and damage-associated molecular patterns. Moreover, one protein, Aldo-keto reductase family 1 member C3 (AKR1C3), is present in eight out of nine CD and absent in all UC samples. Digital IHC analysis reveal a higher percentage and an increased expression intensity of AKR1C3-positive epithelial cells in CD compared to UC and in controls compared to inflammatory bowel disease (IBD). Conclusion and Clinical Relevance Overall, the results suggest that microproteomics is an adequate tool to highlight protein patterns in IBD. IHC and digital pathology might support future differential diagnosis of UC and CD.